Solidão e pensamento em Hannah Arendt - Sousa, Clara Moura (2022)
In this dissertation, we approach the concept of loneliness in Hannah Arendt in her double perspective. For Arendt, loneliness happens as a paradox, at the same time that it reveals itself as a fundamental condition of all human life, it is made as an experience contrary to the basic needs of the human condition. This is because loneliness is revealed as the greatest totalitarian consequence for victims of concentration camps, as well as evidence of the very activity of thought, that is, withdrawing from the common environment to carry out the contemplative task of reflection. To expose this relationship, we first used the work The Human Condition (2007), in order to contextualize the activities that, according to Arendt, constitute an active life. Then, we made the relationship between the concept of masses and isolation, loneliness and totalitarianism and, finally, we present the concept of solitude, differentiating it from the others already identified, for this, we used the work Origins of Totalitarianism (1969). In the second part, in order to elucidate the activityof thinking, we brought the exposition on thoughtlessness, seen by Arendt as the cause for what she called the banality of evil, and this discussion was what motivated the author in her analysis of the activity of thinking. thought. For the second part, we used the works The Life of the Spirit (2000), Responsibility and Judgment (2004) and again, The Human Condition (2007) in order to examine and finalize our research with the concept of plurality, which will serve as a base concept. for all research.